Ultrasound-Detected Metabolic Dysfunction-Associated Steatotic Hepatopathy (MASH) Prevalence in Type 2 Diabetes Patients Attending Primary Care - Yasir, Muammar Basheer; Gaiz, Al-Mottesembellah Abdalruhman; Jaleel, Noor Abdulredha (Journal of medical and pharmaceutical sciences, 2025)
Metabolic dysfunction-associated steatotic hepatopathy (MASH) is a common hepatic complication in patients with type 2 diabetes mellitus (T2DM), and its underdiagnosis in primary care often delays timely interventions and increases the risk of advanced liver disease. This study aimed to determine the prevalence of ultrasound-detected MASH in T2DM patients attending primary care and examine its association with demographic and clinical factors. Methods: A cross-sectional observational study was conducted on 500 T2DM patients aged 30–80 years who attended three primary care clinics between January and June 2025. Abdominal ultrasonography was performed to detect hepatic steatosis using standardized criteria, and demographic and clinical data, including age, sex, body mass index, diabetes duration, and liver enzyme levels, were collected. Statistical analysis was performed using SPSS, with subgroup comparisons by age and sex. MASH was identified in 199 patients (39.8% of the total). The prevalence increased steadily with age, from 11.1% in the 30–39 group to 58.3% in those aged 70–80. Females showed a slightly higher overall prevalence (41.1%) than males (38.7%), with a marked increase after the age of 50 years. Patients with MASH were significantly older than those without non-MASH patients (58.3 vs. 52.7 years, p < 0.01). In conclusion, ultrasound-detected MASH is highly prevalent in T2DM patients, particularly among older adults and postmenopausal women, with age emerging as the most significant risk factor. Therefore, routine ultrasound screening should be incorporated into diabetes care protocols, especially for patients > 50 years of age, to enable timely interventions and reduce the burden of chronic liver disease.
Keywords: MASH; Type 2 Diabetes Mellitushepatic steatosis; ultrasound; primary care; age-related prevalence